(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the rate of postoperative complications and associated factors in hepatectomy for hepatocellular carcinoma (HCC). Materials and Methods: A retrospective cross-sectional study was conducted on 95 patients with HCC who underwent hepatectomy at Binh Dan Hospital from January 2022 to July 2025. Preoperative liver function was assessed using the Child–Pugh classification, ALBI score, and MELD score. Postoperative complications and associated factors were statistically analyzed. Results: The overall postoperative complication rate was 29.5%. Factors significantly associated with complications included comorbidities (p=0.048), previous hepatectomy (p=0.037), open surgery (p=0.046), operative time >180 minutes (p=0.003), and blood loss ≥500 mL (p=0.002). Higher ALBI and MELD scores showed a trend toward increased risk of complications. Conclusion: Hepatectomy for HCC demonstrated an acceptable complication rate. Postoperative complications were associated with comorbidities and surgical factors, particularly prolonged operative time and increased blood loss. ALBI and MELD scores may assist in preoperative liver function assessment.